The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1093/genetics/132.3.651
|View full text |Cite
|
Sign up to set email alerts
|

XRS2, a DNA repair gene of Saccharomyces cerevisiae, is needed for meiotic recombination.

Abstract: The XRS2 gene of Saccharomyces cerevisiae has been previously identified as a DNA repair gene. In this communication, we show that XRS2 also encodes an essential meiotic function. Spore inviability of xrs2 strains is rescued by a spo13 mutation, but meiotic recombination (both gene conversion and crossing over) is highly depressed in spo13 xrs2 diploids. The xrs2 mutation suppresses spore inviability of a spo13 rad52 strain suggesting that XRS2 acts prior to RAD52 in the meiotic recombination pathway. In agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
18
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…Our results indicate that xrs2 and rad5O cells are proficient in the repair of at least a single chromosomal DSB. This is quite consistent with the observation of a partial diploid-specific repair of corresponding diploid cells to y-irradiation (30,54).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results indicate that xrs2 and rad5O cells are proficient in the repair of at least a single chromosomal DSB. This is quite consistent with the observation of a partial diploid-specific repair of corresponding diploid cells to y-irradiation (30,54).…”
Section: Discussionsupporting
confidence: 92%
“…Previous experiments have shown that meiotic and mitotic phenotypes of xrs2A cells are very similar to those of radSOA cells, implying that XRS2 and RAD5O are involved in homologous recombination in similar ways (30). Here, we confirm these results by showing that xrs2zX affects MAT switching similarly to radSOA, leading us to speculate that XRS2 also encodes or regulates a 5'-to-3' exonuclease activity.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations